Depressive symptoms and the general health of retired professional footballers compared with the general population in the UK: a case–control study. Issue 9 (8th September 2019) - Fernandes, Gwen S; Parekh, Sanjay M; Moses, Jonathan; Fuller, Colin W; Scammell, Brigitte; Batt, Mark Edward; Zhang, Weiya; Doherty, Michael
Abstract : Objectives: To determine the prevalence of depressive symptoms and general health of male ex-professional footballers compared with general population controls. Methods: 572 retired professional footballers and 500 general population controls in the UK were assessed by postal questionnaire. Anxiety and depressive symptoms were assessed using the Hospital Anxiety and Depression Scale and a threshold score of ≥11 was used to indicate probable caseness. General health was ascertained using the Short Form-12 Health Survey Questionnaire quality of life (QoL) tool; self-reported comorbidities, analgesic usage and body pain; and Index of Multiple Deprivation based on postcode data. Mood was assessed using the Positive and Negative Affect Scale and sleep using the Medical Outcome Survey. Linear regression analysis was used to determine adjusted relative risk with 95% CI and adjusted for age, body mass index, comorbidities, body pain and medication usage. Results: The prevalence of depressive symptoms in retired professional footballers was 5.66% compared with 5.76% in the general population and anxiety prevalence was also comparable (12.01% vs 10.29%; all p>0.05). However, footballers had lower physical and mental component scores compared with controls (p<0.01). They also reported significantly more sleep problems, more negative mood profiles and more widespread body pain (adjusted relative risk (aRR) 1.88, 95% CI 1.15 to 3.09). They also reported greater pain medication usage compared with controls (aRR 1.54, 95% CI 1.26 to 1.89). However, compared with controls, they were 26% (95% CI 15% to 37%) less likely to report comorbidities, especially heart attacks (aRR 57%, 95% CI 27% to 74%) and diabetes (aRR 61%, 95% CI 37% to 76%). Conclusions: The prevalence of depressive symptoms and anxiety symptoms and probable caseness in ex-professional footballers is comparable with general population controls. However, ex-footballers reported lower health-related QoL, more widespread body pain and higher analgesic usage. Conversely, lower reporting of diabetes and heart attacks indicates potential long-term physical health benefits of professional football.